KETOKSIKAN AKUT TABLET EFFERVESCENT DARI EKSTRAK DAUM SIRIH ( Piper betle L.) PADA TIKUS PUTIH BETINA GALUR WISTAR - Farida Hayati; Retno Murwanti; Wahyu Utaminingrum (Jurnal Ilmiah Farmasi, 2007)
A research on acute toxicity of effervescent tablet from Piper betle leaf extractum on wistar albino female rats was done. This research aimed to determine acute toxicity potential of effervescent tablet from piper betle leaf extractum, evaluated clinical symptom that perhaps occur due to the giving of effervescent tablet, single dosage orally on 24 hours to 15 days observation. The research uses female rats, which are divided into 5 groups. Group I was negative control with aquadest. Group II was given sample with 0,38 g/kgBW dosage. Then, succesively group III with 1,03 g/kgBW dosage, group IV with 2,79 g/kgBW dosage and group V was given test sample with highest dosage, that was 7,50 g/kgBW dosage. On the basis of data analysis result having been performed both quantitively and qualitatively, it could be said that in general, the giving of effervescent tablet from Piper betle leaf extractum single dosage orally on female rats from 0,38 g/kgBW dosage to highest level (7,50 g/kgBW) or approximately 19,74 times of therapy dosage, didn't cause toxic effect which causing damage on lung, liver, kidney, heart, spleen, stomach and intestine. It didn't cause mortality on research animal. So we can determine the quasi LD^, that was bigger than 7,50 g/kgBW, according to Loomis criteria (1978), that acute toxicity potential of effervescent tablet from piper betle extractum was practically not toxic category. Thus based on ANOVA result with 95 % significance level, it could be said that the giving of effervescent tablet from piper betle leaf extractum didn't show significant differences to average body weight changes and organ weight.